Comorbidities and autopsy findings of COVID-19 deaths and their association with time to death: a systematic review and meta-analysis - Martín-Martín, Jaime; Martín-Cazorla, Fernando; Suárez-Pérez, Juan; Rubio-Lamia, Leticia Olga; Martín-de-las-Heras, Stella (My University, 2022)
Objective: Examination of postmortem findings can help establish effective therapeutic strategies to reduce mortality. The aim of this study was therefore to review complete autopsy cases and their postmortem findings and comorbidities associated with death caused by COVID-19, in order to establish a profile of the deceased and the likelihood of time to death. Methods: A systematic review was carried out following the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and meets Cochrane criteria recommendations (PROSPERO registration number CRD 42020209649). An electronic search in the databases Pubmed, Scopus, Web of Science, Wiley Online Library, and Scientific Electronic Library Online (SciELO) was performed. Results: The search strategy yielded a total of 25 articles where 140 cases of complete autopsies were reported. The most prevalent comorbidity was vascular diseases. Patients with vascular disease, heart disease, and diabetes died significantly in a shorter period of time. Autopsies mainly focused on the lungs. The proliferative phase of Diffuse Alveolar Damage (DAD) was the most reported in the microscopic postmortem findings, and these patients died in a shorter period of time. However, individuals aged over 80 years significantly presented fibrotic phase of DAD at the time of death. The kidney was the second most affected organ with thrombosis and tubular damage, followed by the liver with congestion and necrosis. Conclusion: Given that accurate information of complete autopsies findings is still scarce, it is necessary to perform complete autopsies by examining organs other than the lungs in order to provide information to improve new treatment strategies in patients with a high risk of mortality.
Keywords: COVID-19; SARS-CoV-2; autopsy; comorbidities; forensic medicine; mortality